1983
DOI: 10.1136/adc.58.9.732
|View full text |Cite
|
Sign up to set email alerts
|

Computerised nutritional data management in neonatal intensive care.

Abstract: We report the application of computerised data recording, reporting, and analysis to a study of growth and nutrition in a group of preterm and low birthweight infants requiring complex parenteral and enteral nutritional treatment. Materials and methodsThe hardware of the minicomputer based data management system comprises a Digital Electronics DE-FD II computer system consisting of a LSI 11/23 microprocessor with 64 K bytes of random access memory and 2.04 M bytes of floppy disk storage. Input/output (I/O) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Excessive guidelines and rules on a printed paper form clutter it and may confuse the health-care provider, increasing the risk of error or miscalculation. Electronic decision support is an effective tool to design parenteral nutrition for preterm VLBW infants; 24,27,28 however, as shown in this study, its use remains limited. Preterm VLBW infants have unique nutrition requirements that usually require individual parenteral nutrition preparation for each patient.…”
Section: Discussionmentioning
confidence: 93%
“…Excessive guidelines and rules on a printed paper form clutter it and may confuse the health-care provider, increasing the risk of error or miscalculation. Electronic decision support is an effective tool to design parenteral nutrition for preterm VLBW infants; 24,27,28 however, as shown in this study, its use remains limited. Preterm VLBW infants have unique nutrition requirements that usually require individual parenteral nutrition preparation for each patient.…”
Section: Discussionmentioning
confidence: 93%
“…The study population consisted of all infants born alive at between 24 and 28 weeks gestation within (Yu 1977;Yu et al 1979;Wood & Yu 1980: Yu etal. 19816;Wilson et al 1983) and neonatal complications (Yu & Wood 1978;Yu & Hollingsworth 1979;Obeyesekere et a/. 1980: Yu et al 19826;Hawgood et al 1984) in these preterm infants at QVMC have previously been reported.…”
Section: Methodsmentioning
confidence: 88%